An Analysis on Various Policies and Solutions of Municipal Waste Management Services: a Case Study of Mcd: A Critical Analysis of Municipal Waste Management Policies and Solutions in Indian Cities (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Municipal solid waste management (MSWM) is one of the majorenvironmental problems of Indian cities. Improper management of municipal solidwaste (MSW) causes hazards to inhabitants. Various studies reveal that about90% of MSW is disposed of unscientifically in open dumps and landfills,creating problems to public health and the environment. In the present study,an attempt has been made to provide a comprehensive review of thecharacteristics, generation, collection and transportation, disposal andtreatment technologies of MSW practiced in India. Municipal Solid Waste Management (MSWM) is one of themost problematic and neglected aspect of Indian Cities. The high populationgrowth and industrialization put strain on the basic infrastructural andmunicipal services. Presently, in Delhi the municipal solid waste generatedabout 6000 to 8000 metric tonnes per day and quantity of this has beenconsistently rising over the years. Delhi had an average size of 5.06 personsin 2005. Assuming a similar average household size, and a population of 15-20million, there would be 4-5 million households in NCT of Delhi today, thesebecoming the largest source of solid waste generation. Starting fromcollection, transportation and disposal, the Municipal Solid Waste suffers fromweak administrative and managerial problems. With this background the present articleis an endeavour to examine the spatial and temporal aspects of waste managementfacilities i.e. generation, storage and collection, transportation, disposal,and processing. The data has been analyzed using simple statistical techniqueskeeping 12 zones as unit of observation. The study concludes that, there werespatio-temporal variations in the quantity of waste generation in all MCDzones. The spatial analysis of the number of receptacles, vehicles andsafai-karamcharies reveals that their availability gradually declines from coreto periphery zones of MCD. Presently, all existing three landfills (Bhalswa,Gazipur and Okhla) are fully packed and overflowing. Among four landfill sites,Bhalswa is receiving maximum garbage from six zones of MCD whereas Gazipur,Okhla and Narela-Bawana followed it. Simultaneously, it is necessary to reducethe burden on landfill sites in the near future. There is also an urgent needto increase the numbers and efficiency of Composting and Energy Productionplants from the municipal solid waste because composting can only provideanswer to problem of MSW.